An Update on Clinicopathological and Molecular Features of Plexiform Fibromyxoma - Hsuan-An Su; Hsu-Heng Yen; Chih-Jung Chen (Canadian Journal of Gastroenterology and Hepatology)
Plexiform fibromyxoma is a rare and newly described gastric mesenchymal tumor with only 121 reported cases in the literature. Our understanding of plexiform fibromyxoma requires updating since the first case has been reported by Takahashi et al. 12 years ago. The present review summarized reported cases in the literature, and both clinical and pathological aspects of plexiform fibromyxoma were comprehensively discussed. Plexiform fibromyxoma usually causes nonspecific or bleeding signs or symptoms, and therefore clinical recognition of the disease is challenging. Plexiform fibromyxoma is of benign nature without any metastasis or recurrence reported, and more conservative surgical treatment should be considered.